PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE (TEAMS GAMES TOURNAMENT) TGT PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS II SDN 04 TALAOK KABUPATEN PESISIR SELATAN - Radha Pratiwi Sarinaldi; Muhammadi; Reinita; Fikhen Tri Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of grade II students in the subject of Pancasila Education. Students tend to be passive, lack critical thinking, and have difficulty understanding the material because the learning method does not actively involve them. The purpose of this study is to describe the improvement of learning quality through the optimization of teaching modules, learning implementation, and student learning outcomes. This research is a Class Action Research (PTK) with a qualitative and quantitative approach, carried out in two cycles which include the stages of planning, implementation, observation, and reflection. The subjects of the study are teachers and 15 students of grade II for the January-June 2024/2025 semester. The results of the study showed a significant improvement in all aspects. In Cycle I, the achievement of the teaching module was 85.93% at the first meeting and increased to 90.25% at the second meeting. The activity of teachers and students increased from 82.14% to 89.28%. The average learning outcomes of students in the first cycle reached 77.80% (category B). In Cycle II, the achievement of teaching modules increased to 96.42%, teacher and student activities reached 92.85%, and learning outcomes increased to 90.28% (category A). Thus, the actions taken have proven to be effective in improving the quality of the learning process and outcomes of Pancasila Education in grade II of SDN 04 Talaok.